2023
DOI: 10.1007/s00775-023-01999-y
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and anti-biofilm activity of silver nanoparticles biosynthesized with Cystoseira algae extracts

Abstract: Antimicrobial resistance is an ever-growing global concern to public health with no clear or immediate solution. Silver nanoparticles (AgNPs) have long been proposed as efficient agents to fight the growing number of antibiotic-resistant strains. However, the synthesis of these particles is often linked to high costs and the use of toxic, hazardous chemicals, with environmental and health impact. In this study, we successfully produced AgNPs by green synthesis with the aid of the extract of two brown algae—Cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Nevertheless, some comparisons can be drawn which support the advantages of the nanoparticles included in this study. Comparing the results of the present study with silver and gold nanoparticles produced with extracts of the brown seaweeds Cystoseira tamariscifolia and Cystoseira baccata, the MIC values for the non-biofilm-producing bacteria are at much lower concentrations with the biogenic U. pinnatifida nanoparticles [48]. Other authors reported that silver nanoparticles synthesized in Sargassum wightii (average size 48.78 nm) were toxic to S. aureus at a MIC of 130 µg/mL [49], while particles produced in Turbinaria conoides (up to 80 nm) showed a MIC of 64 and 8 µg/mL against P. aeruginosa and S. aureus, respectively [50].…”
Section: Antibacterial Activity Of Up Extract Ag@up and Au@upmentioning
confidence: 65%
See 2 more Smart Citations
“…Nevertheless, some comparisons can be drawn which support the advantages of the nanoparticles included in this study. Comparing the results of the present study with silver and gold nanoparticles produced with extracts of the brown seaweeds Cystoseira tamariscifolia and Cystoseira baccata, the MIC values for the non-biofilm-producing bacteria are at much lower concentrations with the biogenic U. pinnatifida nanoparticles [48]. Other authors reported that silver nanoparticles synthesized in Sargassum wightii (average size 48.78 nm) were toxic to S. aureus at a MIC of 130 µg/mL [49], while particles produced in Turbinaria conoides (up to 80 nm) showed a MIC of 64 and 8 µg/mL against P. aeruginosa and S. aureus, respectively [50].…”
Section: Antibacterial Activity Of Up Extract Ag@up and Au@upmentioning
confidence: 65%
“…On the other hand, no measurable MIC or MBC values were observed for the Au@UP nanoparticles, even at the highest tested concentration of 11.81 µg/mL. Notably, the Ag@UP nanoparticles demonstrated to be even more potent than the antibiotics used as a control (ampicillin and kanamycin; MIC of 40 µg/mL for E. coli and 60 µg/mL for P. aeruginosa and S. aureus), reaching MIC values more than 20 times lower and an average of 5 times lower, compared with silver nitrate (Table 1) [48]. Few reports associate UP extracts with antibacterial activity, which is mostly due to interference of fucoidans with bacterial adhesion to human cells in culture [25].…”
Section: Antibacterial Activity Of Up Extract Ag@up and Au@upmentioning
confidence: 95%
See 1 more Smart Citation
“…It was shown that smaller and round-shaped particles [ 21 ] demonstrate higher antimicrobial activity. Researchers attribute the higher antibacterial activity of these NPs to their greater release of silver ions [ 39 ]. Contrary to expectations, this study found that bigger cube-shaped particles (AgNPs-2) exhibited five times higher antimicrobial effectiveness compared to smaller round-shaped ones (AgNPs-1) against all tested microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers suggest three main mechanisms for the antimicrobial activity of AgNPs such as the formation of reactive oxygen species (ROS), the ion release process, and non-oxidative mechanisms [ 39 ]. The effectiveness of a non-oxidative mechanism or contact killing depends on the contact surface area and surface-to-volume ratio (SA:V).…”
Section: Discussionmentioning
confidence: 99%